Understanding European Union Normative Power: Assessing the Construction of the Norms of Human Rights and Market Liberalization in the EU's relationship with Russia - Ahonen, Staci (University of Ottawa (Canada), 2011)
The European Union's (EU) identity as a nonnative power rests in its ability to construct norms within itself and in third countries. Russia has proven challenging for the EU's norm construction. Through constructivist analysis this thesis attempts to understand the EU's process of norm construction with Russia and domestically and consequently its construction of a nonnative identity. Looking at the period between 2000 and 2008, this thesis presents two main arguments. First, in the EU's attempt to construct its norms of human rights and market liberalization it faced difficulties because as the context shifted, other norms, deemed more important, triumphed over the norms of human rights and market liberalization. This resulted in three identifiable nonnative shifts. Secondly, it focuses on the domestic formation of norms and argues that member states playa significant role in the EU's difficulty to construct norms, in that they have been unable to speak with one voice on human rights and market liberalization.
Keywords: Political Science, International Relations.